Pelanggaran Etika Dalam Rekayasa Laporan Keuangan Pada PT. Dutasari Citra Laras - Wardani, Endah; Paramitha, Dewi; Wowor, Afelini Michelle; Mukti, Nanda Danur Setiya; Shofa, Ghaitsa Zhahira; Saridawati, Saridawati (Indonesian Journal Publisher, 2024)
Internal accountants may violate ethical standards by manipulating accounting data to make a business's financial performance appear better than it actually is. However, unethical behavior on the part of government accountants, for example, can manifest as incorrectly carrying out audit duties as a result of receiving more compensation than the specified amount from the entity whose financial statements are being examined. This research aims to determine ethical violations in the accounting code of ethics.